NEW STAGE OF AUTOMATION DOCUMENT FLOW DEVELOPMENT – WORKING WITH PROJECT DOCUMENTATION IN XML FORMAT - Vladislav I. Denisov; Olga N. Lutsenko; Viktoriya V. Lapkovskaya; Nikita M. Teplyakov (Известия Томского политехнического университета: Промышленная кибернетика)
The relevance of the study is caused by the need to solve the problem faced by design specialists working in accordance with SS R 58367-2019 «Onshore oil field development» in relation to the approval of the Ministry of Construction of the Russian Federation on 12.08.2022 Government Decree No. 87) in XML format according to the provided XML schema. The main aim: digitalization of document flow in the form of solution for providing project documentation in XML format when designing facilities related to the oil and gas complex. Object: development of digital transformation in terms of document flow automation. Subject: document flow automation for project documentation in accordance with the requirements of the Ministry of Construction of the Russian Federation. Methods: evaluation and analysis of existing literature and solutions; development of a tool for collective work on a package of interrelated documents in Word format and XML schema. Results. An extensive analysis of the current state of digitalization of electronic document flow was carried out. The authors proposed the solution automating generation of design documentation for facilities related to the oil and gas complex.